Karakterisasi Tanah Rawa Pasang Surut Delta Pulau Rimau Untuk Mendukung Land Aplikasi Limbah Cair Pabrik Kelapa Sawit - Bakri Bakri; Warsito Warsito; Y. Karimudin (Seminar Nasional Lahan Suboptimal, 2019)
Bakri B, Warsito W, Karimudin Y. 2019. Characterization of raw land in Pulau Rimau to support liquid waste application land palm oil factory. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 90-96. Palembang: Unsri Press.The study aimed to determine the physical and chemical properties of soil to support Land Application of palm oil mill effluent. The research method is carried out by survey method by taking soil samples at several depths. The results showed pH (2.98 - 2.93), C org (38.22 - 61.62 g / kg), N tot (0.84 - 0.95), P brey 1 (1.35 - 1 , 80 mg / kg), K-dd (0.19 - 0.32), Na (0.55 - 1.09 cmol / Kg), Ca (1.8 - 3.23 cmol / kg), Mg ( 0.55 - 1.81 cmol / kg), CEC (17.40 - 19.58 cmol / kg), KBL (14.94 - 32%), Sand (36.99 - 40.94%), Dust ( 40.63 - 55.57%), Clay (7.55 - 22.38%), BD (0.74 - 1.08 g / cm³), RPT (60 - 72%), Permeability (0.27 - 3.45 cm / hour). The results of the analysis show that nutrient-poor soils, but the physical condition of the soil is quite helpful for the media providing land applications for palm oil mill effluent.Keywords: palm oil mills, soil properties, waste